Changes in global histone acetylation pattern in somatic cell nuclei after their transfer into oocytes at different stages of maturation - Fulka, Helena (Molecular reproduction and development, 2008)
In our study, we have examined the pattern of global histone modification changes in somatic cell nuclei after their transfer into mouse oocytes at different stages of maturation or after their parthenogenetic activation. While germinal vesicle (GV) staged immature oocytes are strongly labeled with anti-acetylated histone H3 and H4 antibodies, the signal is absent in both metaphase I and metaphase II oocytes (MI, MII). In contrast, the oocytes of all maturation stages show a presence of trimethylated H3/K4 in their chromatin. When somatic cells were fused to intact or enucleated GV oocytes, both the GV and the somatic cell nucleus showed a very strong signal for all the antibodies used. On the other hand, when somatic cells nuclei that are AcH3 and AcH4 positive before fusion are introduced into either intact or enucleated MI or MII oocytes, their acetylation signal decreased rapidly and was totally absent after a prolonged culture. This was not the case when anti-trimethyl H3/K4 antibody was used. The somatic cell chromatin showed only a slight decrease in the intensity of labeling after its transfer into MI or MII oocytes. This decrease was, however, evident only after a prolonged culture. These results suggest not only a relatively higher stability of the methylation modification but also some difference between the oocyte and somatic chromatin. The ability to deacetylate the chromatin of transferred somatic nuclei disappears rapidly after the oocyte activation. Our results indicate that at least some reprogramming activity appears in the oocyte cytoplasm almost immediately after GV breakdown (GVBD), and that this activity rapidly disappears after the oocyte activation.
Keywords: fertilizace in vitro; Oogenesis; proteinmethyltransferasy; metylace; Histone Acetyltransferases; Fertilization in Vitro; histonacetyltransferasy; techniky jaderného přenosu; Protein Methyltransferases; histonmethyltransferasy; Methylation; ženské pohlaví; Hybrid Cells; histonlysin-N-methyltransferasa; Histones; oocyty; Mice; oogeneze; hybridní buňky; histony; Animals; Histone-Lysine N-Methyltransferase; Histone Methyltransferases; myši; Female; Nuclear Transfer Techniques; zvířata; Oocytes